(untitled) (Al-Academy, 2018)
The popular art movement emerged in the mid-fifties in Britain in parallel with its appearance in America.. It was linked to contemporary social reality and what distinguishes this art is the most sophisticated and less aesthetic means and the most blatant in the field of media, ie back to the image used in the media, journalism, magazines, television and photo Which reflect the reality of the neutral artist. This research included the methodological framework represented by the research problem that emerged from pop art as a new experimental vision that emerged in the twentieth century and the importance of the research and its objectives and limits and the definition of terms. The theoretical framework dealt with evolution Technology, media and consumer culture in popular art, as well as the research procedures of the research community, sample and research tool and analysis of samples and the results and conclusions reached by the researcher, including: 1-Pop art is a reaction to professional concepts in terms of extension in terms of the most common elements as in the Jasper Jones samples. 2-Emphasis on the principle of compilation in the work of art